PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PADA PT MOKA TEKNOLOGI INDONESIA - Shania Zuliana Harahap; Cahyo Pramono; Hasrul Azwar (Ensiklopedia Education Review, 2021)
This study aims to determine the effect of reward and punishment on the employee performance of PT Moka Teknologi Indonesia. In this study uses a quantitative approach, with sample of 25 respondents. The data analysis technique use is multiple regression analysis which serves to prove the research hypothesis. Based on results, the t count value of the reward variable is 0,251, it can be concluded that the reward has not significant effect on the performance of employee of PT Moka Teknologi Indonesia. The t count value of the punishment variable is 0,018, it can be concluded the punishment variable has a positive and significant effect on the performance of employee PT Moka Teknologi Indonesia.  Reward and punishment simultaneously has a positive effect on performance of employee of PT Moka Teknologi Indonesia. The results R square is 70,7%, which means that the reward and punishment variable has an effect on performance of employee variable. While the remaining 29,3% has an effect by other variable not in this study. Keywords: punishment, reward, employee performance